Assessing contraceptive use as a continuum: outcomes of a qualitative assessment of the contraceptive journey - Rebecca G. Simmons; Jami Baayd; Megan Waters; Zoë Diener; David K. Turok; Jessica N. Sanders (BMC, 2023)
Abstract Background Contraceptive use is often a multi-decade experience for people who can become pregnant, yet few studies have assessed how this ongoing process impacts contraceptive decision-making in the context of the reproductive life course. Methods We conducted in-depth interviews assessing the contraceptive journeys of 33 reproductive-aged people who had previously received no-cost contraception through a contraceptive initiative in Utah. We coded these interviews using modified grounded theory. Results A person's contraceptive journey occurred in four phases: identification of need, method initiation, method use, and method discontinuation. Within these phases, there were five main areas of decisional influence: physiological factors, values, experiences, circumstances, and relationships. Participant stories demonstrated the ongoing and complex process of navigating contraception across these ever-changing aspects. Individuals stressed the lack of any "right" method of contraception in decision-making and advised healthcare providers to approach contraceptive conversations and provision from positions of method neutrality and whole-person perspectives. Conclusions Contraception is a unique health intervention that requires ongoing decision-making without a particular "right" answer. As such, change over time is normal, more method options are needed, and contraceptive counseling should account for a person's contraceptive journey.